Regulation of the Twist target gene tinman by modular cis-regulatory elements during early mesoderm development - Yin, Zhizhang; Xu, Xiao-Lei; Frasch, Manfred (Development, 1997)
The Drosophila tinman homeobox gene has a major role in early mesoderm patterning and determines the formation of visceral mesoderm, heart progenitors, specific somatic muscle precursors and glia-like mesodermal cells. These functions of tinman are reflected in its dynamic pattern of expression, which is characterized by initial widespread expression in the trunk mesoderm, then refinement to a broad dorsal mesodermal domain, and finally restricted expression in heart progenitors. Here we show that each of these phases of expression is driven by a discrete enhancer element, the first being active in the early mesoderm, the second in the dorsal mesoderm and the third in cardioblasts. We provide evidence that the early-active enhancer element is a direct target of twist, a gene encoding a basic helix-loop-helix (bHLH) protein, which is necessary for tinman activation. This 180 bp enhancer includes three E-box sequences which bind twist protein in vitro and are essential for enhancer activity in vivo. Ectodermal misexpression of twist causes ectopic activation of this enhancer in ectodermal cells, indicating that twist is the only mesoderm-specific activator of early tinman expression. We further show that the 180 bp enhancer also includes negatively acting sequences. Binding of even-skipped to these sequences appears to reduce twist-dependent activation in a periodic fashion, thus producing a striped tinman pattern in the early mesoderm. In addition, these sequences prevent activation of tinman by twist in a defined portion of the head mesoderm that gives rise to hemocytes. We find that this repression requires the function of buttonhead, a head-patterning gene, and that buttonhead is necessary for normal activation of the hematopoietic differentiation gene serpent in the same area. Together, our results show that tinman is controlled by an array of discrete enhancer elements that are activated successively by differential genetic inputs, as well as by closely linked activator and repressor binding sites within an early-acting enhancer, which restrict twist activity to specific areas within the twist expression domain.
Keywords: Drosophila; tinman; mesoderm; patterning